Percepción de los clientes sobre el marketing de la empresa Inversiones IBB Iquitos año 2024 - Tanchiva Flores, Jose Alexander (2025)
This research project aimed to describe the perception of marketing at Inversiones IBB, a company based in Iquitos, Peru, in 2024. The type of research proposed was basic, with a quantitative approach, the level was descriptive, with a non-experimental, cross-sectional design. The population consisted of 64 distributor clients of the company. Data was collected using a survey questionnaire. The results revealed that 91% of clients perceived the company's marketing as good. The survey findings highlighted a high appreciation from customers towards the product (91%) and price (66%) dimensions. This positive perception is attributed to the company's ability to understand customer needs in depth, build strong relationships, and effectively differentiate itself from competitors. Moreover, the product has been highly valued by customers, with key indicators such as textile quality, a wide variety of designs, and a good quality-price ratio standing out. Despite these positive results, the analysis identified areas for improvement, as customers rated the place (75%) and promotion (91%) dimensions as regular. The company's current location and visibility are perceived as irrelevant, hindering the reach to new customers and the development of a positive and solid image. Additionally, promotional campaigns and the use of digital marketing (social media) have not generated the expected impact and failed to successfully connect with the target audience's expectations. Nevertheless, the company has strengths, thanks to its understanding of the customer and the quality of its product, but it must strive to improve its physical presence, enhance promotional campaigns, and effectively utilize digital marketing to optimize its market positioning. The Cronbach's Alpha coefficient, calculated for this research, reached a value of (0.856), exceeding the acceptable value of (0.70) according to the range table. Therefore, this result demonstrates a good internal consistency in the measurement scale, ensuring the reliability of the instrument used.